Fagopyrum esculentum Alters Its Root Exudation after Amaranthus retroflexus Recognition and Suppresses Weed Growth - Gfeller, Aurélie; Glauser, Gaétan; Etter, Clément; Signarbieux, Constant; Wirth, Judith (Frontiers in Plant Science, 2018)
Weed control by crops through growth suppressive root exudates is a promising alternative to herbicides. Buckwheat (Fagopyrum esculentum) is known for its weed suppression and redroot pigweed (Amaranthus retroflexus) control is probably partly due to allelopathic root exudates. This work studies whether other weeds are also suppressed by buckwheat and if the presence of weeds is necessary to induce growth repression. Buckwheat and different weeds were co-cultivated in soil, separating roots by a mesh allowing to study effects due to diffusion. Buckwheat suppressed growth of pigweed, goosefoot and barnyard grass by 53, 42 and 77 % respectively without physical root interactions, probably through allelopathic compounds. Root exudates were obtained from sand cultures of buckwheat (BK), pigweed (P) and a buckwheat/pigweed mixed culture (BK-P). BK-P root exudates inhibited pigweed root growth by 49 %. Characterization of root exudates by UHPLC-HRMS and principal component analysis revealed that BK and BK-P had a different metabolic profile suggesting that buckwheat changes its root exudation in the presence of pigweed indicating heterospecific recognition. Among the 15 different markers, which were more abundant in BK-P, tryptophan was identified and four others were tentatively identified. Our findings might contribute to the selection of crops with weed suppressive effects.